2017
DOI: 10.3892/mmr.2017.7777
|View full text |Cite
|
Sign up to set email alerts
|

Isoimperatorin ameliorates osteoarthritis by downregulating the mammalian target of rapamycin C1 signaling pathway

Abstract: Osteoarthritis (OA) is the most common disease of the joints, and is characterized by the breakdown of cartilage and degradation of the extracellular matrix. OA causes a high level of patient suffering and incurs large societal costs; however, the current strategies for treating OA are restricted due to limited understanding of the underlying molecular and cellular mechanisms. In the present study, the beneficial effects of isoimperatorin (Iso) were investigated using an experimental mouse model of OA, and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Local application of rapamycin by intra-articular injection may be a potential therapy for OA (Takayama et al, 2014). Other drugs such as isoimperatorin and glucosamine can also activate autophagy and improve cell homeostasis by inhibiting mTOR pathway (Ouyang et al, 2017) (Figure 1). In addition, isoimperatorin improve the pathological changes induced by OA by reducing the expression of matrix metallopeptidase 13 (MMP13), RUNX family transcription factor 2 (RUNX2), collagen type X alpha 1 chain (COL10A1) and vascular endothelial growth factor A (VEGFA).…”
Section: Status Of Oa Therapeutics Targeting Autophagy Signaling Pathwaymentioning
confidence: 99%
“…Local application of rapamycin by intra-articular injection may be a potential therapy for OA (Takayama et al, 2014). Other drugs such as isoimperatorin and glucosamine can also activate autophagy and improve cell homeostasis by inhibiting mTOR pathway (Ouyang et al, 2017) (Figure 1). In addition, isoimperatorin improve the pathological changes induced by OA by reducing the expression of matrix metallopeptidase 13 (MMP13), RUNX family transcription factor 2 (RUNX2), collagen type X alpha 1 chain (COL10A1) and vascular endothelial growth factor A (VEGFA).…”
Section: Status Of Oa Therapeutics Targeting Autophagy Signaling Pathwaymentioning
confidence: 99%
“…ISO exerts inhibitory activity on the NO pathway, which may further contribute to its anti‐asthmatic activity (Huang et al, 2012; Matsuda et al, 2005). A large‐dose and long‐term administration of ISO may ameliorate osteoarthritis without any adverse effects (Ouyang, Jiang, Fang, Cui, & Cai, 2017; Tong, Xin, & Chen, 2017). In addition, we demonstrated that ISO restrained the activation of P38 MAPK in MCs, which is consistent with the result that ISO significantly decreases the phosphorylation of P38 MAPK in the lungs of asthmatic mice and LPS‐induced RAW 264.7 macrophages (Guo et al, 2012; Wijerathne et al, 2017), whereas the phosphorylation of ERK and P38 MAPK in activated MCs is not influenced by DEX (Koranteng et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Many small molecule compounds and natural plant components play protective roles in OA by activating autophagy, such as isoimperatorin, delphinidin, celastrol, curcumin and astragaloside IV ( Liu, Meng, Jing, & Zhou, 2017 ; Ouyang, Jiang, Fang, Cui, & Cai, 2017 ; Lee et al, 2020 ; Xiao et al, 2020 ; Dai et al, 2021 ). Baicalin protects chondrocytes against the degradation of ECM through activating autophagy via miR-766-3p/AIFM1 axis ( Li, Cheng, & Liu, 2020 ).…”
Section: Drugs Targeting Autophagy For Osteoarthritis Treatmentmentioning
confidence: 99%